A residual strain regulation strategy based on quantum dots for efficient perovskite solar cells. Issue 2 (14th December 2022) - Xu, Yinyan; Ren, Yingke; Cheng, Sheng; Zhang, Lun; Niu, Pujun; Lyu, Mei; Lu, Hongbo; Wang, Mingkui; Zhu, Jun
Abstract : A simple strategy is developed to simultaneously release tensile strain and passivate defects in an FA-based perovskite using CsPbI3 QDs, achieving a PCE of 23.3%. Abstract : Lead halide perovskite film exhibits excellent optoelectronic properties. The currently most common preparation method usually needs a conductive-annealing process, which inevitably leads to residual strain and defects, hindering the performance of the resulting perovskite solar cells (PSCs). In this work, we develop a residual strain regulation (RSR) strategy in which an appropriate amount of ligand-capped CsPbI3 quantum dot (QD) solution is used as the antisolvent during the preparation process of (CH(NH2 )2 )0.95 Cs0.05 PbI3 perovskite films. In this strategy, not only do the lattice-matching CsPbI3 QDs act as heterogeneous nucleation centers, but also the ligands attach to the perovskite film's surface, which significantly regulates the crystallization kinetics and releases the residual strain during the annealing process. The strategy successfully delivers multiple effects: an enlarged grain size, fewer defects, reduced nonradiative recombination and higher charge transfer efficiency. Therefore, the device shows a PCE of 23.32%, higher than that of a control device of 21.61%. First-principles calculations are performed to study the electronic structure of the perovskite films under strained conditions. We believe that this facile approach provides a novel strain engineering strategy for PSC technology.